Bella Broomstick - Kuenzler, Lou.; Cheng, Kyan (London : Scholastic Children's Books, 2016)
After failing the entrance exam to Creepy Castle School for the third time, Bella Broomstick is sent into the Person World, where she is forbidden to do magic while being fostered by a non-magical couple.
3-6.
3-6
Keywords: Blacks -- Juvenile fiction; Foster Children -- Juvenile fiction; Magic -- Juvenile fiction; Blacks -- Fiction; Fantasy; Foster Children -- Fiction; Magic -- Fiction; Blacks -- Fiction; Foster children -- Fiction; Magic -- Fiction; Fantastic fiction; Humorous fiction